Vagal stimulation and laryngeal electromyography for recurrent laryngeal reinnervation in children. (12th June 2019) - Caloway, Christen L.; Diercks, Gillian R.; Randolph, Gregory; Hartnick, Christopher J.
Abstract : Ansa‐to‐recurrent laryngeal nerve (ANSA‐RLN) reinnervation procedures are now often first‐line treatments for some children with unilateral vocal fold immobility. Although many describe that children with prolonged denervation and true vocal fold atrophy should not undergo this procedure, there has been no gold‐standard means of identifying true denervation. Here, we describe a novel technique using evoked vagal electromyography to predict degree of chronic nerve injury prior to recurrent laryngeal nerve reinnervation in children. This is a simple, readily available technique that may play an important role in predicting likelihood of success with pediatric ANSA‐RLN reinnervation. Laryngoscope, 130:747–751, 2020